Beyond Basics: Advanced Insights into Reinsurance Theory and Practice - Mussa Charles Juma; Salum Ismail Mlaponi (Beyond Basics: Advanced Insights into Reinsurance Theory and Practice, 2024)
Reinsurance and its design provide a competitive advantage to the primary insurer to increase its profit. The effectiveness, capacity and efficiency of the local and international reinsurance market directly and indirectly control that of the local and international insurance markets respectively. The primary insurers’ risks are not optimally diversified. The primary insurance companies do specialize technically and geographically in order to adventure their underwriting expertise and increase profits. Proportional reinsurance provides capital to the insurers to underwrite more risks and hence increase their underwriting capacity. On the other hand, non-proportional reinsurance stabilizes the ups and downs of losses over time and provides protection against the catastrophic events. The mobilization of underwriting capacity on local and international scale is essential to offer the amount of insurance cover essential for many of developing and developed world’ risks, including catastrophe losses resulting natural disasters, contributes to local and international economic development and stability. The purpose of this book is to provide advanced insights into the reinsurance theory and practice. Chapter one examines the nature, uses and importance of reinsurance. It traces the development of reinsurance globally and regionally specifically Africa and Tanzania. The chapter examines the types, methods and forms of reinsurance and their uses. Chapter two analyses the Tanzania reinsurance market, its capacity, reinsurance cycle and its trend. It examines the participants of the reinsurance market, the accreditation procedures for non-resident reinsurance companies and brokers. The chapter describes the mandatory cession share to local and regional reinsurers. Chapter three examines the nature, features and uses of facultative reinsurance. It presents the types of facultative reinsurance, the advantages and disadvantages to the reinsured. Chapter four analyzes the concept and features of treaty reinsurance, the advantages and disadvantages of it, methods and forms of arranging treaty reinsurance. Chapter five examines the nature, features, uses and types of proportional reinsurance. It features the factors affecting the cession, retention rates and commission rates. Chapter six analyses the non-proportional reinsurance. It examines the features, uses and types of non-proportional reinsurance. Chapter seven examines pricing non-proportional reinsurance contracts. Optimization problems in reinsurance are increasingly using modern techniques of neural networks, telematics and other machine learning models rather than the exposure rating, experience rating, frequency and severity probability models. This chapter presents the machine learning programming methods and provides their difference from the traditional pricing methods. Lastly, chapter eight analyses a reinsurance programme design. It describes the factors which affect the design of the reinsurance programme and the reinsurance optimization. In each of the chapters, there are worked examples and practical exercises which enhance the understanding of the reader. This book is written targeting the bachelor degree and master’s degree candidates in insurance programmes. Insurance professionals and practitioners working in the field of reinsurance programme design and pricing will also find this book valuable to them if they wish to revive their reinsurance knowledge.